METHODS OF TEACHING THE COURSE "FOOD MICROBIOLOGY" AND THE FORMATION OF GENERAL SUBJECT COMPETENCIES FOR HIGHER EDUCATION STUDENTS MAJORING IN "FOOD TECHNOLOGY" - Прилипко, Татьяна; Руснак, Леся (SWorldJournal, 2024)
The management of food safety, which used to be limited to the control of finished products (now this function is entrusted to the state), now consists in the implementation of a number of precautionary measures at various stages of the supply of food pro